Glucose in the hypothalamic paraventricular nucleus regulates GLP-1 release - Ma, Yue (JCI Insight, 2020)
Glucokinase (GK) is highly expressed in the hypothalamic paraventricular nucleus (PVN); however, its role is currently unknown. We found that GK in the PVN acts as part of a glucose-sensing mechanism within the PVN that regulates glucose homeostasis by controlling glucagon-like peptide 1 (GLP-1) release. GLP-1 is released from enteroendocrine L cells in response to oral glucose. Here we identify a brain mechanism critical to the release of GLP-1 in response to oral glucose. We show that increasing expression of GK or injection of glucose into the PVN increases GLP-1 release in response to oral glucose. On the contrary, decreasing expression of GK or injection of nonmetabolizable glucose into the PVN prevents GLP-1 release. Our results demonstrate that gluco-sensitive GK neurons in the PVN are critical to the response to oral glucose and subsequent release of GLP-1.